Development of Posbindu Model in Increasing Compliance of Hypertension Patients With a Local Cultural Approach - Yogisutanti, Gurdani; Suhat, Suhat (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
The lack of community participation in posbindu activities is due to lack of public knowledge, community awareness of non-communicable diseases, poor attitudes and behavior. It is necessary to create a posbindu model based on community needs. The aim of this study is to develop a Posbindu (Integrated Service Post) model using a local cultural approach. Qualitative approach using in-depth interviews with 4 informants aimed at obtaining more in-depth information and Focus Group Discussion (FGD) were attended by 10 participants, consist of 4 males and 6 females, whose ranged from 38-55 years. FGD analysis resulted in several themes, namely: treatment compliance, health education, treatment seeking behavior, family support, policies, and the posbindu model with a local cultural approach. Obtained a posbindu development model with a local cultural approach, according to the needs of the community. The Posbindu model developed using a local cultural approach, specifically Sundanese culture, aligns with the cultural background of the informants. By creating a Posbindu model tailored to the community's needs, it is expected to enhance community participation in Posbindu activities, thereby improving compliance with hypertension treatment. Health promotion programs using local culture, such as during botram activities, have proven effective in increasing public knowledge about hypertension